HEGEMONI DALAM NOVEL JALAN MENIKUNG KARYA UMAR KAYAM: PERSPEKTIF ANTONIO GRAMSCI - Mukhajir, Alif; Rapi, Muhammad; Faisal, Faisal (Fakultas Bahasa dan Sastra Indoensia, 2026)
This study aims to describe the hegemony of the ruling class and cultural hegemony in Umar Kayam’s novel Jalan Menikung. This study employs a qualitative descriptive method, analysing the data obtained in accordance with the theoretical framework used. The data utilised in this study consists of textual passages from the novel, focusing on phrases, sentences and paragraphs within Umar Kayam’s Jalan Menikung. The results of this study indicate the existence of hegemonic control exercised over the character Harimurti through a form of consent-based domination carried out by the authorities, namely the Intel. Furthermore, cultural hegemony was identified, encompassing societal beliefs, Javanese culture, and modern culture, which exert hegemony both directly and indirectly.